1997
DOI: 10.1046/j.1570-7458.1997.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the performance of Cicadulina leafhoppers on flight mills with that to be expected in free flight

Abstract: Flight mills are commonly used to assess the relative flight performance of migratory insects, but uncertainties about the rate of energy expenditure on the mill mean that absolute estimates of flight endurance are not usually attempted. In this paper we describe how we measured the power delivered to a lightweight flight mill by tethered Cicadulina storeyi China leafhoppers (Homoptera: Cicadellidae), and compared this to estimates of the power they use to maintain free flight. Our results showed that the leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 9 publications
0
46
0
Order By: Relevance
“…ßight (via a ßight mill) is frequently an overestimation of the actual linear distance traveled between two points. Thus, ßight mill tests are not aimed to accurately estimate the ßight capacity of test insects, but are most useful as a comparative tool to evaluate ßight potential within the species (Riley et al 1997). It allows estimation of ßight capacity in relation to different preßight-ßight conditions or different physiological status of tested insects such as gender, age, mating, size (Hughes and Dorn 2002).…”
Section: Discussionmentioning
confidence: 99%
“…ßight (via a ßight mill) is frequently an overestimation of the actual linear distance traveled between two points. Thus, ßight mill tests are not aimed to accurately estimate the ßight capacity of test insects, but are most useful as a comparative tool to evaluate ßight potential within the species (Riley et al 1997). It allows estimation of ßight capacity in relation to different preßight-ßight conditions or different physiological status of tested insects such as gender, age, mating, size (Hughes and Dorn 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measurements of flow field in the LEV of M. sexta showed that the LEV was continuous across the thorax and runs to each wingtip [6]. Although flow visualizations on free and tethered dragonflies have shown some similar properties [12], the tethered flights can nevertheless convincingly reproduce the scenarios of free flight [13], in both kinematics [14] and force generation [15]. Hence, studies on the aerodynamics of insects in free flight are consistently pursued [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…However, much of the information on the dispersal ecology of H. halys required to enhance landscape-level monitoring and management tactics of this pest is essentially unknown. The widely used tethered ßight mill technique (e.g., Smithe andFurniss 1966, Liu et al 2011) can be used to establish the baseline ßight capacity of H. halys (D.-H.L., unpublished data), but not to readily assess its natural movement in the Þeld (Riley et al 1997, Taylor et al 2010. Other techniques are required to assess its movement within the landscape.…”
mentioning
confidence: 99%